Top Grafting Performance of Some Cocoa (Theobroma cacao L.) Clones as Affected by Scion Budwood Number - Fakhrusy Zakariyya; Fitria Yuliasmara (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2015)
Reducing budwood number is an efficient effort to overcome problemsrelated with limited scion materials. The objective of this research was to studythe effect of scion budwood number in some clones on the performance of graftedcocoa seedlings. The research was conducted at Kaliwining Research Station,Indonesian Coffee and Cocoa Research Institute, Jember, Indonesia at an elevationof 48 m above sea level. Layout for this study used factorial with 2 factors inrandomized complete block design, with four replications for every treatment.The first factor was clone type, namely MCC 02 and Sulawesi 1; whereas the secondfactor was number of grafted scion budwood, namely one, two, and three graftedbudwoods. There was no interaction between clone and number of scion budwoodfor variables of shoot length, stem girth, content of total chlorophyll, chlorophylla, and chlorophyll b. Meanwhile, there was interaction for stomatal conductanceand stomatal diffusion resistance. Clone significantly affected photosynthesisand stomatal diffusion resistance, while number of scion budwood affected significantlythe shoot length. Photosynthesis activity of MCC 02 was higher comparedto Sulawesi 1. In average, stomatal diffusion resistance of Sulawesi 1 was higherthan MCC 02. The shoot length of one grafted budwood was higher than thetwo or three grafted budwood.